Investigation of the defect complexes in highly Mg-doped LiNbO₃ crystals by ⁹³Nb NMR method - Yatsenko, A.V.; Yevdokimov, S.V.; Sugak, D.Yu.; Solskii, I.M. (Functional Materials, 2014)
Angular dependence of the line width of the <⁹³Nb NMR spectrum central transition for LiNbO₃ crystal with congruent composition and for the samples with high Mg concentration was experimentally investigated. Having the experimental results compared with the results obtained by computer simulation, it has been concluded that the most probable type of defects in magnesium doped LiNbO₃ crystals are (4MgLi²⁺ + 4VLi) defect complexes when four Li vacancies and three MgLi²⁺ ions being localized in the seven nearest positions to the central MgLi²⁺.